Sistem Pengembangan Workflow Manajemen Kerja (Studi Kasus: PT. Chevron Pacific Indonesia) - Lazuardi Dio Ramadhan; Fajar Pradana; Faizatul Amalia (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Information technology is something that is needed at this time, one of which is to help company management because it produces information quickly. PT Chevron Pacific Indonesia has succeeded in determining one of them with good management work related to work deadlines. The company PT Chevron Pacific Indonesia has information technology in the field of work management, but currently in work management to make a work process must make a business process, then after it is finished with a system that will assign employees to it. This causes problems, namely the difficulty of direct assignments to employees and the process of work being carried out. PT Chevron Pacific Indonesia needs a system to assist the process of making and assigning employees. In making this system use workflows which are workflow processes and can be carried out related to the workflow provided to employees. In representing workflows performed, Business Process Model Notation (BPMN) will be discussed, which is a standard for modeling business processes. In the end the system can make business processes, assign employees, and complete tasks. This system was built on a web platform and was approved by whitebox, blackbox testing and usability testing with the Usability Scale System method to produce acceptable categories, namely systems created according to user desires.